Why migrate: For study or for work? - Elise S. Brezis (Economies, 2016)
Over the past decades, globalization has led to a huge increase in the migration of workers, as well as students. This paper develops a simple two-step model that describes the decisions of an individual vis-à-vis education and migration, and presents a unified model, wherein the two migration decisions are combined into a single, unique model. This paper shows that under the plausible assumption that costs of migration differ over the human life cycle, the usual brain drain strategy is sub-optimal. With an increase in globalization, the brain drain strategy will be replaced by the strategy of migration of students.
Keywords: F22; I23; J24; 330; brain drain; globalization; higher education; human capital; migration; mobility